Quantitative assessment of the response of maxillary sinuses to occlusive load - A. V. Tscymbalistov; A. A. Kopytov; L. V. Pazhnsky; V. I. Tyazhlov (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2015)
It is believed that odontogenic sinusitisiscaused by spread of infection from periapical tissues of teeth. Importance of clinical topographic ratio between bottom of the maxillary sinus and apexes of chewing teeth» is referred to quite often, but usually the data proposed are received by describingrelatively small samples from collections ofmacerated skulls, which makes it impossible to determine anyregularities in structure of the facial skull and in location of the alveolar bone and teeth